2002
DOI: 10.1098/rspb.2002.2052
|View full text |Cite
|
Sign up to set email alerts
|

How an orchid harms its pollinator

Abstract: Certain orchids produce owers that mimic the sex pheromones and appearance of female insects in order to attract males by sexual deception for the purpose of pollination. In a series of eld experiments, we found that the sexually deceptive orchid, Chiloglottis trapeziformis, can have a negative impact on its wasp pollinator Neozeleboria cryptoides. Male and female wasps, however, were affected differently by the orchid's deceit because of their different roles in the mimicry system. Male wasps could not discri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 23 publications
1
72
1
Order By: Relevance
“…Pollination systems with reproductive behavior were significantly more specific than pollination systems with foraging behavior (t 21.24 = 2.31, P = 0.03) (Figure 2), suggesting that orchids using specialized pollinators are also more specialized in pollination. Our findings thus do not support the suggested nestedness in mutualistic associations (91); however, only the rewarding orchidpollinator associations are mutualistic, whereas deceptive pollination can be seen as a parasitic relationship (146).…”
Section: Specificity In Pollinationcontrasting
confidence: 99%
See 2 more Smart Citations
“…Pollination systems with reproductive behavior were significantly more specific than pollination systems with foraging behavior (t 21.24 = 2.31, P = 0.03) (Figure 2), suggesting that orchids using specialized pollinators are also more specialized in pollination. Our findings thus do not support the suggested nestedness in mutualistic associations (91); however, only the rewarding orchidpollinator associations are mutualistic, whereas deceptive pollination can be seen as a parasitic relationship (146).…”
Section: Specificity In Pollinationcontrasting
confidence: 99%
“…This finding was demonstrated in pollinators of sexually deceptive orchids, e.g., solitary bees, that cease responding to individual sex pheromone blends when they are associated with unreceptive females (sexually deceptive orchids) (5). Thynnine males avoid multiple visits to sexually deceptive orchids by keeping away from their flowering sites (96,146). Such behavior may have evolved to avoid wasting time with nonreceptive females, but it is unlikely to lead to switching between species-specific pheromone signals.…”
Section: Pollinator Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…One well-described example is the broadlip bird-orchid Chiloglottis trapeziformis (family Orchidaceae), which attracts male thynnine wasps Neozeleboria cryptoides (family Tiphiidae), resulting in successful pollination (Wong & Schiestl, 2002;see also, de Jager & Peakall, 2015). It is suggested that the chemical mimicry is an effective longrange attraction, while the visual appearance of the callus structures on the labellum can lead to pseudo-copulation.…”
Section: Introductionmentioning
confidence: 99%
“…'call') to attract flying males (Oakwood 1990;Wong & Schiestl 2002). In this regard, competition among males is intense with the operational sex ratio strongly biased towards males, and males respond rapidly to calling females (Alcock 1981;Alcock & Gwynne 1987;Peakall 1990;Wong & Schiestl 2002). Apart from the actual mating, female wasps also rely on males to carry them to their food source and to return them to a suitable oviposition site (Given 1954;Peakall 1990).…”
Section: Introductionmentioning
confidence: 99%